2015
DOI: 10.1007/s00231-015-1585-4
|View full text |Cite
|
Sign up to set email alerts
|

Forming method of micro heat pipe with compound structure of sintered wick on grooved substrate

Abstract: in chips and dramatically reducing reliability and performances [1][2][3]. So thermal control has become a hot issue for the high-power electronic components with high heatflux, which urgently needs solving. Miniature/micro heat pipes have become ideal radiating devices for high heatflux chips because of their high heat conductivity and no need for extra electronic driving. As a heat pipe's heat transfer performance is mainly determined by its wick structure, and the compound structure of sintered wick on a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Moreover, the contact angle plays a major role in enhancing the capillary pressure, since the capillary pressure is proportional to the contact angle. It is proven that the contact angle of an anodised surface is less than that of a nonanodised surface [16]. The capillary pressure generated in the grooved wick is represented as:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the contact angle plays a major role in enhancing the capillary pressure, since the capillary pressure is proportional to the contact angle. It is proven that the contact angle of an anodised surface is less than that of a nonanodised surface [16]. The capillary pressure generated in the grooved wick is represented as:…”
Section: Resultsmentioning
confidence: 99%
“…Li et al [16] tested an MHP by incorporating a compound structure of sintered wick on a grooved structure as the capillary material. From the studies [8][9][10][11][12][13][14][15][16], it is understood that the new kind of wick structures exhibited a significant effect on the heat transfer enhancement of heat pipes over the same with traditional wick structures. Although different wick structures are available for better heat transfer, the base materials of wick structures are mostly copperbased materials, which are slightly heavier than lightweight materials such as aluminium.…”
Section: Introductionmentioning
confidence: 99%
“…The micro-sintered heat pipe has a high heat transfer capacity, but the manufacturing process is complicated. Moreover, the structure of sintered capillary wick is easily damaged, and the copper powder particles in the wick structure are prone to fall off when subjected to heavy load deformation [15]. However, the capillary wick structure of microgroove heat pipe is directly formed on the inner wall of the pipe [16].…”
Section: Introductionmentioning
confidence: 99%
“…It is concluded that the plough-extrusion cutting performance of 60 degree extrusion angle cutter is the best.Nowadays, with the rapid development of microelectronic technology, the heat flux density of microelectronic products has increased dramatically. Because of the characteristics of high heat transfer efficiency, high heat dissipation property, good isotherm property and no need of extra power source, heat-pipes with wick micro-groove structure are widely used to solve the thermal control and conduction of products with high heat flux density [1][2][3][4][5]. The manufacturing forming of wick micro-groove structure is the key problem of micro heat pipe technology.…”
mentioning
confidence: 99%